Molecular identification and physiological functional analysis of NtNRT1.1B that mediated nitrate long-distance transport and improved plant growth when overexpressed in tobacco - Wu, Changzheng; Xiang, Yucheng; Huang, Pingjun; Zhang, Mingfa; Fang, Ming; Yang, Weiqin; Li, Wenrui; Cao, Fengchun; Liu, Lai-Hua; Pu, Wenxuan; Duan, Shuhui (Frontiers in Plant Science, 2023)
Although recent physiological studies demonstrate that flue-cured tobacco preferentially utilizes nitrate (NO3−) or ammonium nitrate (NH4NO3), and possesses both high- and low-affinity uptake systems for NO3−, little is known about the molecular component(s) responsible for acquisition and translocation in this crop. Here we provide experimental data showing that NtNRT1.1B with a 1,785-bp coding sequence exhibited a function in mediating NO3− transport associated with tobacco growth on NO3− nutrition. Heterologous expression of NtNRT1.1B in the NO3− uptake-defective yeast Hp△ynt1 enabled a growth recovery of the mutant on 0.5 mM NO3−, suggesting a possible molecular function of NtNRT1.1B in the import of NO3− into cells. Transient expression of NtNRT1.1B::green fluorescent protein (GFP) in tobacco leaf cells revealed that NtNRT1.1B targeted mainly the plasma membrane, indicating the possibility of NO3− permeation across cell membranes via NtNRT1.1B. Furthermore, promoter activity assays using a GFP marker clearly indicated that NtNRT1.1B transcription in roots may be down-regulated by N starvation and induced by N resupply, including NO3−, after 3 days’ N depletion. Significantly, constitutive overexpression of NtNRT1.1B could remarkably enhance tobacco growth by showing a higher accumulation of biomass and total N, NO3−, and even NH4+ in plants supplied with NO3−; this NtNRT1.1B-facilitated N acquisition/accumulation could be strengthened by short-term 15N-NO3− root influx assays, which showed 15%–20% higher NO3− deposition in NtNRT1.1B-overexpressors as well as a high affinity of NtNRT1.1B for NO3− at a Km of around 30–45 µM. Together with the detection of NtNRT1.1B promoter activity in the root stele and shoot–stem vascular tissues, and higher NO3− in both xylem exudate and the apoplastic washing fluid of NtNRT1.1B-transgenic lines, NtNRT1.1B could be considered as a valuable molecular breeding target aiming at improving crop N-use efficiency by manipulating the absorption and long-distance distribution/transport of nitrate, thus adding a new functional homolog as a nitrate permease to the plant NRT1 family.